Association of R156R single nucleotide polymorphism of the ERCC2 gene with the susceptibility to ovarian cancer. (January 2017) - Romanowicz, Hanna; Michalska, Magdalena M.; Samulak, Dariusz; Malinowski, Jakub; Szaflik, Tomasz; Bieńkiewicz, Jan; Smolarz, Beata
Abstract: Aim: The reported study was designed to explore associations between the ERCC2 - R156R gene single nucleotide polymorphism (SNP) and the risk of ovarian cancer. Material and methods: The R156R (C to A, rs238406) polymorphism of ERCC2 gene was investigated by the PCR-RFLP technique in 400 patients with ovarian carcinoma and 400 age- and sex matched non-cancer controls. Blood samples were obtained from patients treated at the Department of Surgical Gynaecology and Gynaecologic Oncology, Institute of Polish Mothers Memorial Hospital between the years 2000 and 2015. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated for each genotype and allele. Results: Genotype distribution of R156R polymorphism of ERCC2 gene was compared between the patients and controls with significant differences (p< 0.05) between the two investigated groups. A possible association was observed between ovarian cancer and the presence of A/A genotype (OR 3.30 95% CI 2.26–4.82, p < 0.0001). The variant A allele of ERCC2 increased the risk of ovarian cancer (OR 2.08 95 % CI 1.70–2.54, p < 0.0001). A relationship was confirmed between ERCC2 R156R polymorphism and ovarian cancer progression, assessed by the degree of histological grades and FIGO staging (p < 0.05). Conclusion: This is the first study, linking R156R polymorphism of ERCC2 gene with ovarian carcinoma incidence. In conclusion, ERCC2 - R156R polymorphism may be connected with the susceptibility to ovarian cancer.